2017
DOI: 10.1101/162024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flat-to-curved transition during clathrin-mediated endocytosis correlates with a change in clathrin-adaptor ratio and is regulated by membrane tension

Abstract: Although essential for many cellular processes, the sequence of structural and molecular events during clathrin-mediated endocytosis remains elusive. While it was believed that clathrin-coated pits grow with a constant curvature, it was recently suggested that clathrin first assembles to form a flat structure and then bends while maintaining a constant surface area. Here, we combine correlative electron and light microscopy and mathematical modelling to quantify the sequence of ultrastructural rearrangements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In the second, clathrin lattices grow flat to their terminal surface area and then bend to create a vesicle (Heuser, 1980). Mixtures of these models have been observed: clathrin sites growing flat, growing curved, or switching between behaviors, even within the same cell (Scott et al, 2018;Bucher et al, 2018). Indeed, clathrin imaging in live cells exhibits varied lifetime dynamics, consistent with this mixed model of endocytosis (Sochacki and Taraska, 2019;Loerke et al, 2011).…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…In the second, clathrin lattices grow flat to their terminal surface area and then bend to create a vesicle (Heuser, 1980). Mixtures of these models have been observed: clathrin sites growing flat, growing curved, or switching between behaviors, even within the same cell (Scott et al, 2018;Bucher et al, 2018). Indeed, clathrin imaging in live cells exhibits varied lifetime dynamics, consistent with this mixed model of endocytosis (Sochacki and Taraska, 2019;Loerke et al, 2011).…”
Section: Introductionmentioning
confidence: 57%
“…These data support a modified version of the constant area model of clathrin curvature. Previous work with electron, live cell fluorescence, and correlative microscopy has shown that in some cell lines (SK-MEL-2 and BS-C-1) (Avinoam et al, 2015;Bucher et al, 2018), flat clathrin curves. Further, in these cells, curvature can occur at the onset, during, or after the complete recruitment of clathrin to the membrane (Scott et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4). Prior studies have suggested that the clathrin:adaptor ratio is a determinant of CCP curvature (Bucher et al, 2018). The clathrin:AP180 protein ratio on synaptic membranes for αβγ-synuclein KO displayed an 1.14 and 2.42 fold increase for heavy and light chain, respectively, suggestive of altered curvature of assembled clathrin lattices.…”
Section: Examining the Role Of α-Synuclein In Clathrin Lattice Curvaturementioning
confidence: 87%